The oncological multidimensional prognostic index is a promising decision-making tool: A real-world analysis in older patients with metastatic colorectal cancer. (December 2022) - Procaccio, Letizia; Bergamo, Francesca; Gatti, Maura; Chiusole, Benedetta; Tierno, Giuseppina; Bergo, Eleonora; Daniel, Francesca; Nappo, Floriana; Maddalena, Giulia; Rasola, Cosimo; Barsotti, Giulia; De Grandis, Maria C.; et al.
Abstract: Background: Approximately 50% of colorectal cancers occur in older patients. International societies recommend geriatric tools to optimise treatment of older patients. Comprehensive Geriatric Assessment (CGA) is a multidimensional assessment used to classify patients as fit, vulnerable, or frail. The CGA-based oncological multidimensional prognostic index (onco-MPI) also classifies patients as high-, intermediate-, or low-risk based on tumour characteristics. We investigated the role of CGA and onco-MPI in older patients with metastatic colorectal cancer (mCRC) in a real-world setting. Methods: Data for consecutive mCRC patients aged ≥70 years were retrieved from a prospectively maintained database from 2010 to 2020. We analyzed patients' and tumours' characteristics, and the CGA domains. Onco-MPI was calculated by a validated algorithm derived from CGA domains. Pearson's test was used to verify whether onco-MPI scores and chemotherapy administration were correlated. Results: The study included 488 mCRC patients with a mean age of 76.1 years. According to CGA, 52% of patients were fit, 28% vulnerable, and 20% frail. According to onco-MPI, 9% were low, 54% intermediate, and 37% high-risk. The median OS was 22.7 months. The following factors improved OS: 0–1 ECOG PS, low onco-MPI, fit based on CGA, chemotherapy administration, and doublet regimen. Chemotherapy administration significantly correlated with onco-MPI scores, leading to a survival gain regardless of the risk subgroups. First-line regimen had no impact on survival across the CGA and onco-MPI categories. Conclusion: CGA and onco-MPI scores confirmed their prognostic impact in older mCRC patients and may aid in decision-making and subgroup stratification in dedicated trials. Highlights: Geriatric assessment in older cancer patients is recommended by current guidelines. We analysed onco-MPI and comprehensive geriatric assessment in older mCRC patients. The study demonstrated the prognostic role of onco-MPI and geriatric assessment. Onco-MPI adds valuable information for proper management of older cancer patients. Therapy was modulated by onco-MPI leading to survival benefit in all subgroups.